2021
DOI: 10.1007/978-3-030-63046-1_20
|View full text |Cite
|
Sign up to set email alerts
|

Lysophospholipids in Lung Inflammatory Diseases

Abstract: The lysophospholipids (LPLs) belong to a group of bioactive lipids that play pivotal roles in several physiological and pathological processes. LPLs are derivatives of phospholipids and consist of a single hydrophobic fatty acid chain, a hydrophilic head, and a phosphate group with or without a large molecule attached. Among the LPLs, lysophosphatidic acid (LPA) and sphingosine-1-phosphate (S1P) are the simplest, and have been shown to be involved in lung inflammatory symptoms and diseases such as acute lung i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 161 publications
1
10
0
2
Order By: Relevance
“…Here, we showed that platelets from severe allergic patients contain altered levels of proinflammatory lipids such as sphingolipids (ceramides (Cer) and sphingomyelins (SM)), arachidonic acid (AA), and lysophospholipids (LPC). These lipids have been reported to be involved in the allergic inflammatory response 29‐31 . In this work, we have detected an increase in Cer and SM in platelets of severe allergic patients.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Here, we showed that platelets from severe allergic patients contain altered levels of proinflammatory lipids such as sphingolipids (ceramides (Cer) and sphingomyelins (SM)), arachidonic acid (AA), and lysophospholipids (LPC). These lipids have been reported to be involved in the allergic inflammatory response 29‐31 . In this work, we have detected an increase in Cer and SM in platelets of severe allergic patients.…”
Section: Discussionsupporting
confidence: 55%
“…These lipids have been reported to be involved in the allergic inflammatory response. [29][30][31] In this work, we have detected an increase in Cer and SM in platelets of severe allergic patients. Cer and SM belong to the family of sphingolipids, and their importance in allergic diseases has been widely studied.…”
Section: Discussionmentioning
confidence: 55%
“…However, as the process relied on cheap starting materials and delivered sufficient amounts of the desired ureas, no systematic optimization work was carried out. 13 C NMR spectra of ureas incorporating a 2,6diisopropylaniline usually showed two signals for the two apparently symmetric isopropyl groups, indicating reduced rotational freedom of this moiety. The carbamates 43 and 45 needed for this study were obtained in moderate to good yields by reacting the appropriate phenyl isocyanate with the corresponding phenol (Scheme 2) in the presence of an excess of ethyl-diisopropylamine as a base.…”
Section: ■ Chemistrymentioning
confidence: 99%
“…ATX , and LPAR1 , are ubiquitously expressed, and based on LPA’s implication in many pivotal cellular processes, the ATX-LPA receptor axis was proposed as a viable target to treat cardiovascular, inflammatory, , and proliferative diseases. , Remarkably, LPAR1-deficient mice showed attenuated vascular leakage and fibrosis in a bleomycin-induced lung fibrosis model . Furthermore, elevated levels of LPA were found in bronchoalveolar lavage fluid (BALF) and exhaled breath condensate from patients with idiopathic pulmonary fibrosis (IPF), , suggesting continuous activation of LPAR1 by its ligand LPA as a key mechanism contributing to fibrosis progression.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation